ANALISIS KINERJA KEUANGAN DAN DANA PIHAK KETIGA SEBELUM DAN SESUDAH PENERAPAN BRANCHLESS BANKING PADA PERUSAHAAN PERBANKAN SYARIAH DI INDONESIA - Ketut Tanti Kustina; Fitriani; IGA Diah Utari (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2022)
Purposes of this study to determine financial performance of Islamic banking before and after branchless banking which measured by ROA’s ratio and determine third-party funds of Islamic banking before and after branchless banking. The research method used in this study is descriptive-quantitative. The process of collecting data by search and observe annual report. Sample used in this study are PT. Bank BRI Syariah, PT. Bank Muamalat, PT. Bank Mandiri Syariah, PT. Bank BTPN Syariah, dan PT. Bank BNI Syariah. The results of T-test shows that ROA’s indicator didn’t show difference significantly between before and after branchless banking and from third-party funds show there’s difference significantly between before and after branchless banking. To improve profitability from ROA, the banking need to improve third-party funds for investment and to increase third-party funds resources, the banking need to promote branchless banking service and motivate people for using this service.